System Performance and Limits of Optical Modulation Formats in Dense Wavelength Division Multiplexing Systems - Agalliu, Rajdi; Lucki, Michal (Elektronika ir Elektrotechnika, 2016)
In this paper we investigate in OptSim software environment the system performance of intensity and phase modulation formats for different network scenarios and dense wavelength division multiplexing grids. OptSim employs the Time Domain Split Step method to implement the signal distribution equation in a fiber. We investigate intensity formats, such as Non Return to Zero, Return to Zero, Carrier-Suppressed Return to Zero and DuoBinary, and phase modulation formats like Differential Phase-Shift Keying and Differential Quadrature Phase-Shift Keying. The main goal is to compare these formats in terms of bit error rate, Q-factor, optical reach and grid limitations for transmission rates 10, 40 and 100 Gbps per channel and discuss the possibilities of increasing their spectral efficiency. We also focus on other advanced solutions such as the polarization division multiplexing combined with phase modulations, coherent detection and advanced digital signal processing which mainly benefits in spectral efficiency, optical signal to noise ratio and chromatic dispersion tolerances. DOI: http://dx.doi.org/10.5755/j01.eie.22.2.9599